The Dot Voting Technique to Improve Narrative Text Writing Skill of the Eighth Graders: Dot Voting Technique to Improve Narrative Text Writing Skill - Anita Apriliyani Ningrum; Siti Musarokah; Jafar Sodiq; Peni Utami (English Language Education Department, Universitas Majalengka, 2023)
Writing used to express and to communicate some ideas. The score of students’ narrative writing skill of eighth graders of one state junior high school in Semarang is under of minimum criteria. The English standard minimum score is 75. Objectives of this research are to know how great Dot Voting technique can improve students’ eighth graders learning motivation in class and to know how high Dot Voting technique increasement of students’ narrative writing skill at the eighth graders of one state junior high school in Semarang. Classroom action research is the research type. The research was conducted in class VIII D of one state junior high school in Semarang. This research used non-test and test instruments to collect the data. The non-test instruments are observation sheet and documentation. The writer used quantitative data in analyzing the data. In first cycle and second cycle, the students have better enthusiasm and participation to follow the activities. At pre-cycle test, their writing average score reached 65.74. In first cycle test when the writer applied the action the students’ writing average score is 74.87 or improves 9.13. In second cycle test, their writing average score reaches 82.09. It means that it improves 7.22 from the first cycle. In second cycle indicates that the teaching process is successful. Based on the result, firstly, to English teachers to use interesting teaching technique in teaching especially in writing skill is Dot Voting technique. Secondly, to students to enrich their narrative text writing skill by using Dot Voting.